At ikke være eller ikke at være – Mladen Dolars stemme - Ugilt, Rasmus (Slagmark - Tidsskrift for idéhistorie, 2018)
In this article I investigate and discuss Mladen Dolar’s philosophy of the voice. In this regard a particular emphasis is put on showing how Dolar through an ingenious engagement with the workings of the voice in a select few of Kafka’s novellas and stories provides a striking account of several philosophical themes and problems. What is at stake is nothing short of the relation of being to nothingness and the question of human freedom.